2022
DOI: 10.1002/solr.202200964
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Surface Modification and Defect Passivation on Tin Oxide–Perovskite Interfaces using Pseudohalide Salt of Sodium Tetrafluoroborate

Abstract: Passivating electron‐transporting layers (ETLs) with alkali salts have demonstrated a facial approach that is essential in healing defective surfaces, consequently improving the functionality and stability of perovskite‐based solar cells (PSCs). Herein, the pseudohalide salt of sodium tetrafluoroborate, whose anions have a higher electronegativity than other halide salts (i.e., iodide and chloride), with the potential to passivate the surface of tin oxide while enhancing the optoelectronic properties of a pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…[32] This can also be confirmed by the presence of F 1s peak (Figure S2d, Supporting Information), which suggest that the singly-bonded OH T s are well passivated by the F T s during the PA-SAMs adsorption. It was previously reported that the surface fluorination is robust enough to compete with and prevent the surface interaction with the hydroxyl groups from moisture at terminal-oxygen sites, that is, the displacement of F T s by OH T s. [33] These F T s on the ITO surface can not only prevent the direct contact of ITO with perovskite active layer, but also effectively passivate perovskite buried defects by forming strong hydrogen and ionic bonds with perovskite lattices. [30] To gain a more comprehensive understanding of the difference in the ITO surface termination induced by the surface reconstruction, complementary Fourier transform infrared spectroscopy (FTIR) measurements were performed at each step of the surface modification.…”
Section: Resultsmentioning
confidence: 99%
“…[32] This can also be confirmed by the presence of F 1s peak (Figure S2d, Supporting Information), which suggest that the singly-bonded OH T s are well passivated by the F T s during the PA-SAMs adsorption. It was previously reported that the surface fluorination is robust enough to compete with and prevent the surface interaction with the hydroxyl groups from moisture at terminal-oxygen sites, that is, the displacement of F T s by OH T s. [33] These F T s on the ITO surface can not only prevent the direct contact of ITO with perovskite active layer, but also effectively passivate perovskite buried defects by forming strong hydrogen and ionic bonds with perovskite lattices. [30] To gain a more comprehensive understanding of the difference in the ITO surface termination induced by the surface reconstruction, complementary Fourier transform infrared spectroscopy (FTIR) measurements were performed at each step of the surface modification.…”
Section: Resultsmentioning
confidence: 99%
“…This combined effect of optimizing the perovskite grain size serves to elevate the overall efficiency, performance, and reliability of perovskite solar cells. Second, the interaction between Pb 2+ and Cl – mitigates leaked current originating from excessive Pb 2+ at crystal grain boundaries, thereby increasing shunt resistance . Third, the dopant of Cl – creates a stronger electric field within the SnO 2 ETL, thereby contributing to lower series resistance at the interface between ETL and the perovskite film …”
Section: Results and Discussionmentioning
confidence: 99%
“…Second, the interaction between Pb 2+ and Cl − mitigates leaked current originating from excessive Pb 2+ at crystal grain boundaries, thereby increasing shunt resistance. 37 Third, the dopant of Cl − creates a stronger electric field within the SnO 2 ETL, thereby contributing to lower series resistance at the interface between ETL and the perovskite film. 38 The incident photon-to-current conversion efficiency (IPCE) spectra and integrated J sc curves are presented in Figure 4b.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of superhalogen (highly electronegative inorganic compounds with greater electron affinities than monoatomic halogens) anionic species, 28,29 ), is proven to be an effective approach [30][31][32][33][34][35] for passivating the vacancies/interstitials of halide anions and/or organic cations with the increased activation energy of ion migration. These superhalogen anions have similar ionic radii to I − ions (the ionic radii of BF 4 − and I − are 218 and 220 pm, respectively), which are expected to substitute I vacancies/interstitials.…”
Section: Why Superhalogens With Aromatic Rings?mentioning
confidence: 99%